nternational legal and foreign advanced experience in the legal regulation of agricultural machinery using ultrafast mobile communications (5G) for Kazakhstan - Karazhan, B.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Ultra-fast mobile technologies are rapidly entering our lives. Fifth-generation mobile communication is a key factor in the further development of these technologies. The proposed article is about international best practices in the development of 5G technologies in agricultural engineering and its legal regulation. The author of the article notes the importance of international cooperation for the benefit of 5G development not only in the Republic of Kazakhstan but also around the world. The article also discusses the existing legal problems of the 5G industry and a certain attempt was made to predict the emergence of future legal challenges. The main method of research was the method of comparative legal analysis of foreign best practices in the development of 5G communications. The central task of this article is to familiarize the circle of experts and specialists of the legislative body with the global trends taking place in the world of telecommunications technologies and their impact on certain sectors of the economy.